PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, STRUKTUR AKTIVA, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Fidiena, Hanifa; Nursiam, Nursiam (ITB AAS Indonesia Surakarta, 2024)
The purpose of this research was to determine the effect of profitability, company growth, asset structure, and company size on capital structure in the transportation and logistics sector on the Indonesia Stock Exchange. The population in this research were all transportation and logistics sector companies totaling 37 companies on the Indonesia Stock Exchange, during the period 2021-2023. The sampling technique used was purposive sampling, with this technique the final sample obtained was 18 companies with 54 analyzed data. The data analysis technique used is the classical assumption test and multiple linear regression analysis using the SPSS 25 application. The results of the analysis show that profitability has no effect on capital structure, growth rate has no effect on capital structure, asset structure has a significant negative effect on capital structure and company size has an effect on capital structure.